“We don’t talk about these things”: Asian American Veterans’ lived experiences and perspectives of suicide risk and prevention - Krishnamurti, Lauren S.; Mignogna, Joseph; Iglesias, Christe’An D.; Rohs, Carly M.; Polzer, Evan R.; Holliday, Ryan; Iwamasa, Gayle Y.; Monteith, Lindsey L. (Frontiers in Psychiatry, 2025)
BackgroundSuicide rates have increased substantially among Asian American, Native Hawaiian, and Pacific Islander Veterans. However, little is known about the context of suicide risk or how best to tailor care for this population, especially as it relates specifically to Asian American Veterans, for whom extant research has been limited. We explored Asian American Veterans’ lived experiences with suicidal thoughts and behaviors, their perspectives regarding suicide risk and prevention, and the broader context in which these occurred.MethodsQualitative interviews were conducted in 2022–2023 with 20 Asian American Veterans with histories of suicidal ideation and/or suicide attempt(s). Interviews explored participants’ identities and values (i.e., for context), as well as their beliefs, experiences and perspectives regarding suicide prevention (e.g., how suicide is discussed among Asian American Veterans, factors that might cause Asian American Veterans to experience suicidal ideation, and how suicide prevention initiatives can be tailored to address the needs of Asian American Veterans). Interview transcripts were analyzed through inductive thematic content analysis.ResultsWe identified four themes relevant to Asian American Veterans’ experiences with suicidal thoughts and behaviors, perspectives on suicide risk and prevention, and the context in which these occurred. First, participants spoke to the “model minority” stereotype and pressure to convey self-discipline and perfectionism and to acculturate to American or Western values, which were also shaped by their own or familial immigration experiences. Second, participants reflected upon their minoritized status within the U.S. military, which often mirrored the sense of “otherness” experienced outside of their military service. While participants described positive overall experiences in the military, they also described experiencing racism during their military service. Third, mental health stigma was salient, shaped by cultural beliefs and perceived as consistent with military culture, deterring disclosure and help-seeking and posing an obstacle for suicide prevention. Lastly, destigmatizing mental healthcare and increasing the visibility of Asian American Veterans seeking mental health services were considered paramount to suicide prevention.ConclusionConsiderations for preventing suicide among Asian American Veterans include addressing the sociocultural factors that shape mental health, suicide risk, and healthcare use. In particular, findings suggest the importance of addressing stereotypes about Asian Americans (e.g., model minority myth), preventing behaviors that contribute to a sense of “otherness,” and increasing the visibility of Asian American Veterans in outreach and messaging to promote help-seeking.